BIN2 phosphorylates the Thr280 of CO to restrict its function in promoting Arabidopsis flowering - Ju, Lan; Dong, Huixue; Yang, Ruizhen; Jing, Yexing; Zhang, Yunwei; Liu, Liangyu; Zhu, Yingfang; Chen, Kun-Ming; Ping, Junai; Sun, Jiaqiang (Frontiers in Plant Science, 2023)
CONSTANS (CO) is a central regulator of floral initiation in response to photoperiod. In this study, we show that the GSK3 kinase BIN2 physically interacts with CO and the gain-of-function mutant bin2-1 displays late flowering phenotype through down-regulation of FT transcription. Genetic analyses show that BIN2 genetically acts upstream of CO in regulating flowering time. Further, we illustrate that BIN2 phosphorylates the Thr280 residue of CO. Importantly, the BIN2 phosphorylation of Thr280 residue restricts the function of CO in promoting flowering through affecting its DNA-binding activity. Moreover, we reveal that the N-terminal part of CO harboring the B-Box domain mediates the interaction of both CO-CO and BIN2-CO. We find that BIN2 inhibits the formation of CO dimer/oligomer. Taken together, this study reveals that BIN2 regulates flowering time through phosphorylating the Thr280 of CO and inhibiting the CO-CO interaction in Arabidopsis.